Peran Leadership Dalam Meningkatkan Kinerja ASN: Suatu Tinjauan Sistematis Literatur - Mulyati Rahmah; Asyfa Nurul Askia; Devi Ramadhani; Boni Saputra; M. Fachri Adnan (CV. ITTC INDONESIA, 2026)
This study aims to analyze the role of leadership in improving the performance of Civil Servants (ASN) in the public sector through a Systematic Literature Review (SLR) approach. This study reviews 20 scientific articles from nationally accredited SINTA journals and Scopus-indexed international journals published during the period 2020–2025. The review focuses on transformational leadership, servant leadership, and digital leadership, as well as their relationship with work motivation, organizational commitment, and public service quality. This research employs a qualitative descriptive method through literature identification, article selection, thematic analysis, and synthesis of previous studies.The results show that leadership has a significant effect on motivation, work discipline, organizational commitment, bureaucratic innovation, and public service quality. Transformational leadership is the most dominant style in improving ASN performance through vision, inspiration, and employee empowerment. In addition, servant leadership enhances job satisfaction, while digital leadership supports digital transformation in bureaucracy.This study concludes that adaptive and innovative leadership plays an important role in strengthening bureaucratic reform and improving the professionalism of civil servants in the public sector.